Effects of magnesium coating on bone‐implant interfaces with and without polyether‐ether‐ketone particle interference: A rabbit model based on porous Ti6Al4V implants. Issue 7 (26th January 2019) - Du, Zhe; Yu, Xiaoming; Nie, Binen; Zhu, Zhonglin; Ibrahim, Muhammad; Yang, Ke; Tan, Lili; Wang, You
Abstract: We investigated the effects of magnesium (Mg) on osteogenesis and bone resorption at a porous structure interface. A three‐dimensional (3D)‐printed porous Ti6Al4V implant coated with Mg was introduced, and polyether‐ether‐ketone wear particles were added to generate an animal model of implant loosening. We also examined the effects of Mg leach liquor on osteoblast/osteoclast gene expression, alkaline phosphatase activity, collagen secretion, tartrate‐resistant acid phosphatase activity, and bone resorption in vitro. Mg inhibited the early stage of osteoclast differentiation and inhibited bone resorption in vitro and in vivo. However, Mg did not enhance osteogenesis in vitro or in vivo in the porous structures or in peripheral areas around the implants. For implants with porous structures, the Mg coating did not improve the osteogenic ability by itself, but could restrain peri‐implant osteolysis, which may make it favorable for use in patients with osteoporosis. Further studies are needed to examine the precise mechanism of Mg‐induced anti‐osteolysis and the long‐term effects of Mg‐coated implants in humans. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 2388–2396, 2019.